Sports injuries. Prevention, diagnosis, treatment, and rehabilitation (Springer, 2012)
In recent years, research studies into sports injuries have provided healthcare professionals with a better understanding of their etiology and natural history. On this basis, novel concepts in the diagnosis and management of these conditions are now being explored. This timely book offers a complete guide to the latest knowledge on the diagnosis and treatment of the full range of possible sports injuries. Individual sections are devoted to biomechanics, injury prevention, and the still emerging treatment role of growth factors, which foster more rapid tissue healing. Sports injuries of each body region are then examined in detail, with special attention to diagnostic issues and the most modern treatment techniques. In addition, pediatric sports injuries, extreme sports injuries, the role of physiotherapy, and future developments are extensively discussed. All who are involved in the care of patients with sports injuries will find this textbook to be an invaluable, comprehensive, and up-to-date reference.'